Strategi Pembelajaran Di Sekolah Mts Al-Fajar Sei Mencirim - Adella Mayza Zuhro; Ayu Lestari Br Ginting; Ahmad Zaki Pane; Bella Puspita; Evita Sari (PT. Banjarese Pacific Indonesia, 2024)
Education is the main foundation in building a superior generation, and learning strategies play a key role in the educational process. This research aims to investigate the learning strategies implemented at MTs Al-Fajar Sei Mencirim. The research method used is a case study with a qualitative approach. Data was collected through classroom observations, interviews with teachers, and documentation. The research results show that MTs Al-Fajar Sei Mencirim applies various innovative and diverse learning strategies, including group discussions. By implementing diverse and innovative learning strategies, MTs Al- Fajar Sei Mencirim is able to create a dynamic learning environment and motivate students to achieve academic achievement and personal development. The implication of this research is the importance of continuing to develop and perfectlearning strategies that suit the needs and development of students in an ever- changing educational era.